Fabrication and performance enhancement of an In2O3/BiVO4 heterojunction for N-butanol gas sensing applications - Xiang-Bing, Li; Sun, Shuang; Hu, Xiang; Qian-Qian, Zhang; Gao, Cheng; Zhou, Hui; Bao-Xu, Wu; An-Qi, Wang; Wen-Yao, Hu; Yi-Jia, Wang; Li-Xiong, Yang; Yang, Bin; et al. (RSC advances, 2024)
Butanol, a highly toxic volatile organic compound, poses significant health risks. Consequently, the creation of efficient gas-sensitive materials for butanol detection holds substantial practical significance. This study employed a secondary hydrothermal technique to synthesize In2O3, BiVO4, and their composite In2O3/BiVO4. Notably, the In2O3/BiVO4 composite exhibited a threefold enhanced response, short desorption time and low operating temperature compared to pure BiVO4. Moreover, the composite demonstrated improved selectivity, certain moisture-proof performance, and prolonged stability. The synthesis strategy, which entailed growing microspherical In2O3 on BiVO4, led to structural modifications, enhanced surface area, increased oxygen adsorption capacity, an enlarged optical bandgap, and improved anti-interference ability of the device. As a result, the formation of an n–n heterojunction between In2O3 and BiVO4 in the composite material translates into an outstanding butanol sensing device.